Social Structure of Mizo Village: a Participatory Rural Appraisal - Lalhmunmawia; Das, Samares Kumar (International Journal of Bio-resource and Stress Management, 2019)
Mizoram in india, the land of Mizo, is the fifth smallest state in India with the highest tribal population. However, there is a dearth of in depth study on social structure of Mizo village. This calls for a better understanding of social structure for planning and implementation of location specific research and development programs. Keeping this in view, a field study was carried out in a purposively selected village named Muthi in Aizawl district of Mizoram to study the social structure through Participatory Rural Appraisal (PRA) to help R&D professionals to plan and implement location specific development programs. Case study was done following the principles and methods of PRA. Data collected through PRA were analyzed and reported through the principles and methods of PRA. Established in 1910, Muthi was a village with three localities. Supply and services included road, path, stair steps, spring, cemetery, community hall, shop, post office, playing ground, and a number of institutions and organisations. Among institutions in the village, Church and Young Mizo Association were most important. Houses were constructed on the top and slope of the hill along the road. Traditionally, houses were rectangular in shape with thatched roof and walls made of weaved bamboo or timber frames with bamboo mat floor, which did not exist at present. Water scarcity was the most important problem in the village which should be solved first.